WHERE THE MINANG MIGRATE, THERE THE TAREKAT IS TAUGHT: PRELIMINARY EXPLORATION OF THE LINEAGE AND ROLE OF THE MINANG-ORIGIN TAREKAT IN MEDAN CITY - Hidayat, Ziaulhaq (LPPM STAI Muhammadiyah Probolinggo, 2023)
This article initially explores the Minang-origin tarekat in Medan City. These Minang-origin tarekats are scattered in various regions and have an activity base in Medan City. The distinguishing element of a Minang tarekat from other communities is related to the ethnic identity within it, both in the doctrines and rituals taught to the tarekat. To understand the tarekat from Minang, a related research question is asked about the genealogy and role of the community from Minang in Medan City. This research found several tarekats from Minang, namely the Tarekat Syattariyah (TS), which has a lineage connected to Shaykh Burhanuddin in Ulakan, Pariaman, the Tarekat Sammaniyah wa Naqsyabandiyah (TSN) related to Shaykh ‘Abd al-Qadim in Belubus, Payakumbuh, the Tarekat Naqsyabandiyah Kadirun Yahya (TNKY) is connected to Shaykh Hasyim in Bukit Tinggi and Shyakh ‘Abd al-Majid in Tanah Datar, and the Tarekat Naqsyabandiyah Yayasan Jabal Abi Qubis (TNYJAQ) from Shaykh Ibrahim’s path in Bonjol, Pasaman. Meanwhile, the role played by the tarekat from Minang relates to spiritual education, such as Sufism recitation, which is actively carried out in surau or at home, and mysticism activities which are practiced according to a specified time. Finally, this study confirms that Minang-origin tarekats in Medan City have an important role in the spiritual education of the people of Medan City.